Acute bilateral angle closure glaucoma induced by methazolamide - Aref AA (Dove Medical Press, 2013)
Ahmad A Aref,1,2 Fouad E Sayyad,2 Bernadete Ayres,2 Richard K Lee21Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, 2Illinois Eye and Ear Infirmary, University of Illinois at Chicago School of Medicine, Chicago, IL, USAPurpose: To report a case of bilateral acute myopia and angle closure glaucoma after ingestion of methazolamide.Methods: An interventional case report of a 70-year-old male who developed bilateral, acute myopia and angle closure glaucoma after ingesting methazolamide tablets for the treatment of normal tension glaucoma.Results: Bilateral anterior chamber shallowing associated with ciliary body edema, supraciliary effusions, and shallow posterior choroidal effusions were documented with slit-lamp photography and high-frequency ultrasonography. Near complete resolution of these signs after discontinuation of methazolamide were also documented.Conclusion: Methazolamide may be associated with secondary myopia and angle closure glaucoma. Discontinuation of methazolamide leads to resolution of this process, as documented by slit-lamp photography and high-frequency ultrasonography.Keywords: glaucoma, glaucoma pharmacology, angle closure glaucoma